Pendampingan Peserta Didik dalam Kecerdasan Spiritual di SMP Muhammadiyah Mataram - Widia Febriana; Rina Komala; Defel Septian; Gozin Najah Rusyada; R. Ayu Ida Aryani; Rahman Prasetyo (Jurnal Ilmiah Pengabdian dan Inovasi, 2023)
The problem of dedication is the low role of the school environment in increasing the spiritual intelligence of Muslim students at SMP Muhammadiyah Mataram. This service aims to 1) analyze the school environment at SMP Muhammadiyah Mataram, 2) analyze the level of spiritual intelligence of Muslim students at SMP Muhammadiyah Mataram, 3) analyze how much influence the school environment has on the spiritual intelligence of Muslim students at SMP Muhammadiyah Mataram. The service population is all Muslim students at SMP Muhammadiyah Mataram with a total of 51 students. Data collection uses questionnaires, observations, interviews, and documentation. The conclusions from the dedication are 1) The school environment is in the medium category, with a percentage of 66.7%, the highest aspects of the school environment, namely school discipline and teacher-student relations, a percentage of 21%. 1) The spiritual intelligence of Muslim participants at SMP Muhammadiyah Mataram is categorized as moderate with a percentage of 51, 1% and a high aspect of spiritual intelligence, namely the social aspect of 26%, 2) There is an influence of the school environment on the spiritual intelligence of Muslim students at SMP Muhammadiyah Mataram.